9x-2=6+8x

Simple and best practice solution for 9x-2=6+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-2=6+8x equation:


Simplifying
9x + -2 = 6 + 8x

Reorder the terms:
-2 + 9x = 6 + 8x

Solving
-2 + 9x = 6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-2 + 9x + -8x = 6 + 8x + -8x

Combine like terms: 9x + -8x = 1x
-2 + 1x = 6 + 8x + -8x

Combine like terms: 8x + -8x = 0
-2 + 1x = 6 + 0
-2 + 1x = 6

Add '2' to each side of the equation.
-2 + 2 + 1x = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 6 + 2
1x = 6 + 2

Combine like terms: 6 + 2 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| (4x+5)^4/5=81 | | 60=-2x-2x+6(x+10) | | 42=7+z/5 | | -64=-4(n-5) | | 2(x+5)+3(x-10)=100 | | 2x-4(x+3)-10=6 | | -(2x+8)=-20 | | x-7=.5x | | -6(n+4)=30 | | 5b+12-2b+6=-15 | | 520=6x+3x+x | | y=3x^2-18x-27 | | 49=10+P/5 | | 4/3x3.14x0.022^3/2 | | 2x-3/9=3x-4/6 | | 2x-3/9=3x-/6 | | 5k-9-2k+3=3k-9 | | (z-8)(z-3)/(z^2+16)(z^2-16) | | .75k-6=2k+5 | | e=g+p/ | | 5x-3y=y-2x | | 12x+6=10x+30 | | 4(3-x)+u=22+2x | | 16=-8+-9y | | 7a-7b=15whatisA-B | | 3/4K-6=2k+5 | | -36a^5b^4/16a^-5b^2 | | Thiswebsiteusescookiestoensureyougetthebestexperienceonourwebsite.Moreinfo5x^2+7=9x/2 | | 15p-30= | | -10x=-24 | | 8-4/x-2=-1/2 | | x+12x=-32 |

Equations solver categories